A Minireview on Biodiscovery in Antarctic Marine Benthic Invertebrates - Avila, Conxita; Angulo-Preckler, Carlos (Frontiers in Marine Science, 2021)
Antarctic marine benthic invertebrates are an underexplored source of natural products for biodiscovery. Bioactive marine natural products from Antarctica are reviewed here for their potential use as drugs, considering the main examples in Porifera (15 species), Cnidaria (eight species), Mollusca (one species), Bryozoa (one species), Nemertea (one species), Echinodermata (six species), and Tunicata (five species). A wide variety of bioactivities are reported here, from antitumoral to antimicrobial activities, as well as against neurodegenerative diseases and others. If we aim to use their chemodiversity for human benefits we must maintain the biodiversity, solving the supply problem, speeding up the process, and decreasing research costs to fully exploit the benefits of biodiscovery in Antarctic Marine Natural Products in a near future in a sustainable way.